Long-Term Outcome of Temporal Lobe Epilepsy Surgery in 621 Patients With Hippocampal Sclerosis: Clinical and Surgical Prognostic Factors - Pereira Dalio, Marina Teixeira Ramalho; Velasco, Tonicarlo Rodrigues; Feitosa, Izabela Dayany Franca; Assirati Junior, João Alberto; Carlotti Junior, Carlos Gilberto; Leite, João Pereira; dos Santos, Antonio Carlos; Alexandre, Veriano; Nakano, Frederico Nakane; Saute, Ricardo Lutzky; Wichert-Ana, Lauro; Sakamoto, Americo Ceiki (Frontiers in Neurology, 2022)
Abstract Temporal lobe epilepsy (TLE) is the most common type of focal epilepsy and is frequently drug-resistant (DR) to antiseizure medication (ASM), corresponding to approximately one-third of the cases. When left inadequately treated, it can worsen the quality of life, cognitive deficits, and risk of death. The standard treatment for drug-resistant TLE is the surgical removal of the structures involved, with good long-term outcome rates of 60-70 % and a low rate of adverse effects. The goal of successful treatment is sustained seizure freedom. In our study, we evaluated sustained long-term (up to 23 years) surgical outcomes in 621 patients with DR-TLE associated with hippocampal sclerosis, who underwent a temporal lobectomy. We analyzed the main predictive factors that influence the surgical outcome related to seizure control, through a longitudinal and retrospective study, using a multivariable regression model. We found that 73,6 % of the patients were free from disabling seizures (Engel Class I), maintained over time in 65% of patients followed up to 23 years after surgery. We found that four independent variables predicted seizure outcomes. The presence of dysmnesic and olfactory aura predicted a less favorable outcome. The history of febrile seizure and the surgical technique predicted a good outcome. Regarding the type of surgical technique, the standard anteromesial temporal lobectomy led to significantly better outcomes (78.6% Engel Class I) when compared to the selective amygdalohippocampectomy via subtemporal approach (67.2% Engel Class I; p=0.002), suggesting that the neuronal networks involved in the epileptogenic zone may be beyond mesial temporal structures. The multivariable regression model with the above-mentioned predictor variables revealed an ExpB=3.627 (N= 621, p < .001), indicating that the model was able to distinguish between patients with a seizure-free. We conclude that epilepsy surgery is a safe procedure, with low rates of postoperative complications and good long-term results.